Wschód czy Zachód? Konflikt (wrogich) narracji w Petersburgu Andrieja Biełego - Polak, Andrzej (Studia Rossica Posnaniensia, 2024)
In this article, Andrei Bely’s novel Petersburg is analyzed in terms of the clash of two hostile narratives – Eastern and Western – that have shaped Russian statehood from the rule of Tsar Peter I. The presence of solutions associated with the West, in the history of Russia, as well as in the social and political system of the Russian state, is considered to be the result of a kind of self-colonization and internal colonization. The author of the article, drawing on terminology developed in post-colonial research, highlights the tensions existing within Russian society at the beginning of the 20th century, which translate into internal divisions in the main characters of the work, in particular the senator Apollon Ableukhov and his son Nikolay. Although they both appear to belong to Western civilization and culture, they in fact pave the way for the victory of a chaos of Eastern provenance, which culminates in the Russian revolutions of the early 20th century.